دراسة تأثير عملية تبريد الخلية الفوتوفولتية على رفع كفاءة أنظمة الهيدروجين الشمسي - لؤي يسير (Tishreen University, 2016)
إن الطاقة الشمسـية والهيدروجين هــي من بين الخيارات المحتملة والبديلة للــوقود الحالي، لكــــــن العائق الرئيســي لتطبيق الطاقـة الشــمسـية وخاصة الخلايا الفوتوفولتية هي انخفاض كفاءتها في تحويل الطاقة بسبب ارتفاع درجة حرارتها، أما الهيدروجين  فيجب إنتاجه بشــــــــــــكل غازي أو سائل قبل استخدامه كوقود ولكن عملية التحويل الرئيسية لإنتاج الهيدروجين تنتج غـــاز ثاني أكســــــيد الكربون  الضار بالبيئة لما تسببه مــن ارتفاع فـــــي درجة حرارة الأرض, في أطار البحث عن حلول لهذه القضايا يأتي هذا البحث ليتحرى التحكم بدرجة حرارة الخلية الفوتوفولتية فــــي محاولـــــــــة لتلافي تأثيرات ارتفاع درجة حرارة الخلية كما يبحث في تأثيرات ذلك على توليد غاز الهيدروجين عن طريق جهاز التحليل الكهربائي للماء بطريقة صديقة للبيئة. أثبتت نتائج التجارب أن نظام التبريد يوقف ارتفاع درجة حرارة الخلية الفوتوفولتية مما عكـــــــس النتائج السلبية لانخفاض كفـــاءة التحويل كما ازداد الناتج الكهربائي للخلية بمقدار 33 % و أظهرت النتائج أيضا أنه عند توصيل الخلية الفوتوفولتية إلى جهاز التحليل الكهربائي للماء فإن تبريد الخلية الفوتوفولتية انعكس بشكل إيجابي على ارتفاع معدل إنتاج الهيدروجين بحدود 26% Solar Energy and Hydrogen are possible replacement options for fossil fuel, But  a major drawback to the full implementation of solar energy, in particular photovoltaic (PV), is the lowering of conversion efficiency of PV cells due to elevated cell temperatures while in operation. Also, hydrogen must be produced in gaseous or liquid form before it can be used as fuel; but its‟ present major conversion process produces an abundance of carbon dioxide which is harming the environment through global warming. In search of resolutions to these issues, this research investigated the application of Thermal Management to Photovoltaic (PV) modules in an attempt to reverse the effects of elevated cell temperature. The investigation also examined the effects of the thermally managed PV module to a Electrolyzer (Hydrogen Generator) for the production of hydrogen gas in an environmentally friendly way. The results of the investigation showed that the cooling system stopped the cell temperature from rising, reversed the negative effects on conversion efficiency, and increased the power output of the module by as much as 33%. The results also showed that the thermally managed PV module when coupled to the hydrogen generator impacted positively with an appreciablely increase of up to 26% in hydrogen gas production.